Practical Investigation of Innovative Sustainable Fashion Design using Plastic Waste (Journal of Fiber Bioengineering and Informatics, 2022)
In order to solve the contradiction between economic development and environmental problems, the trend of recycling strategies increases the value of textiles and other waste in the supply chain. Fashion companies have been trying to develop sustainable clothing made from post-consumer plastic bottles, but few studies have explored the practice and innovation of plastic waste in clothing design from the fashion perspective. Considering the complexity of plastic waste recycling, this article explores the possibility of upgrading and recycling plastic waste in clothing fabrics through the analysis and performance analysis of plastic waste materials. On this basis, the design hypothesis of waste plastics on the sustainability of clothing is proposed to establish the basic framework of the design. According to the design framework, two kinds of waste plastic materials are explored in the pre-experiment. Through the comparison and evaluation of the pre-experiment effect, a feasible scheme is finally selected for the overall design of a clothing series in visual display.
Keywords: Plastic Waste; Clothing Innovation Practice; Sustainable Fashion Design